Analisis Kelengkapan Fasilitas Kesehatan dalam Meningkatkan Kenyamanan Pasien Di Klinik Dental Care Cihanjuang - Nur'aida, Nifal; Hamdan, Hamdan (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Dental Care clinic is a private clinic that serves a variety of dental health services. One of the main problems often faced by this clinic related to service quality is the lack of available medical personnel and limited space facilities. This study uses a descriptive qualitative method that aims to describe or explain the phenomenon in detail and objectively. The results of this study from the indicators of reliability, assurance, and empathy of services performed by Dental Care clinics are good enough in performing service quality. While the responsiveness of the Dental Care clinic is still not optimal because there are still times when the treatment action process is not assisted by the nurse because it is handling other patients.  And also based on physical evidence, namely the infrastructure at the Dental Care clinic is still inadequate where the narrow waiting room can affect patient comfort.